Implementation and Effectiveness of Engineering Noise Control: Evaluation in Malaysia’s Manufacturing Sector - Pravina Deligannu; Azmir, Nor Azali; Shahmir Hayyan Sanusi; Mat Hussin, Shakilla Nur Asimah; Daud Adam; Mohd Hatta Zakaria; Mohd Yunos Talib; Fauziah Kamaruddin; Elaini Wahab; Noor Fazira Ab Aziz; Saifuladili Jaafar; Rohaizad Mohd Daud; et al. (Journal of Advanced Mechanical Engineering Applications, 2026)
Occupational noise-induced hearing disorders, also known as ONRHD remain the most prevalent occupational disease in Malaysia, driven by excessive exposure in the manufacturing sector. This study evaluated the sound pressure level (SPL) as well as implementation and effectiveness of engineering noise controls in three high-risk subsectors: electrical/electronic, metal/steel, and food. A total of 796 machines were assessed using sound level meters (SLM) (Class 1). More than half of the machines (53.5%) exceeded the safe threshold of 82 dBA, while 35.6% operated above the Noise Exposure Limit (NEL) of 85 dBA. Subsector analysis revealed the food industry as the highest risk, with 43.4% of machines exceeding 85 dBA, several surpassing 100 dBA and approaching 110 dBA. The metal/steel subsector recorded 38.3% above NEL, while electrical/electronic subsector had 28.6%, albeit with significant variability across machine groups such as grinders, stamping presses, and air compressors. Of the 184 machines with engineering controls, insulation was the most common (54.3%), yielding an average reduction of –8.2 dBA. Control combinations, such as insulation with distance, achieved greater attenuation (–10.9 dBA), though inconsistent performance was observed, often due to poor selection, design, or maintenance. Notably, 75 machines continued to exceed 85 dBA despite controls, highlighting implementation gaps. There was no significant difference in SPL between machines with and without controls (p>0.05). Overall, only 13.7% of machines required no further intervention. These findings underscore the urgent need for tailored engineering controls guided by octave band analysis, stronger enforcement of noise regulations, and machine-specific mitigation strategies to reduce NIHL risk in Malaysia’s manufacturing sector